2017
DOI: 10.1021/acs.jpcc.6b12059
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Raman Responses of the Vapor-Deposited Tin Selenide Ultrathin Flakes

Abstract: Tin selenide (SnSe) is a newly emerging layered material. SnSe with low dimensionality has been reported as an appealing material with a diverse range of applications such as rechargeable lithium-ion batteries, memory switching devices, solar energy conversion, thermoelectric energy conversion, and near-infrared optoelectronic devices. Here we synthesized SnSe ultrathin flakes on SiO2/Si substrates through simple vapor deposition route and investigated its temperature-dependent Raman spectroscopy behavior with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
103
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 37 publications
6
103
0
Order By: Relevance
“…The extracted χ for mode Ag at 210 cm −1 is −0.0095 cm −1 K −1 . The obtained value for GeSe 2 is much smaller than that for other 2D layered materials such as BP (−0.023 cm −1 K −1 for A 2 g mode), SnS (−0.036 cm −1 K −1 for A 2 g mode), and SnSe (−0.0377 cm −1 K −1 for A 2 g mode), while nearly equal to ReSe 2 (−0.0074 cm −1 K −1 for A g ‐like mode) and in good agreement with the previous report . It was reported that the first‐order temperature coefficients of the Raman active modes were associated with the interlayer interaction between the layers of 2D layered materials .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The extracted χ for mode Ag at 210 cm −1 is −0.0095 cm −1 K −1 . The obtained value for GeSe 2 is much smaller than that for other 2D layered materials such as BP (−0.023 cm −1 K −1 for A 2 g mode), SnS (−0.036 cm −1 K −1 for A 2 g mode), and SnSe (−0.0377 cm −1 K −1 for A 2 g mode), while nearly equal to ReSe 2 (−0.0074 cm −1 K −1 for A g ‐like mode) and in good agreement with the previous report . It was reported that the first‐order temperature coefficients of the Raman active modes were associated with the interlayer interaction between the layers of 2D layered materials .…”
Section: Resultssupporting
confidence: 90%
“…In addition to the room temperature Raman spectroscopy, we also performed the temperature‐dependent Raman spectroscopy, which can provide exact information on thermal expansion, thermal conductivity, and interlayer coupling . In view of convenience, we selected the most intensive Ag mode located at 210 cm −1 for further detailed analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Two peaks located at 32.3 and 55.1 eV can be assigned to the Ge 3d and Se 3d core-level peaks, respectively. [36] The variation of Raman frequency can be determined by: [37] [17] We then obtained the temperature-dependent Raman spectroscopy for the GeSe 2 rhombic flakes (Figure 3); such a study is an efficient way to investigate the thermal expansion, thermal conductivity, and interlayer coupling.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated χ coefficient is −0.00546 cm −1 K −1 for the peak at 210 cm −1 , which is several times smaller than those of other 2D layered materials such as SnSe 2 (A 1g mode, χ = −0.0129 cm −1 K −1 ), [35] MoS 2 (E 1 2g mode, χ = −0.0136 cm −1 K −1 ), [38] and SnSe (B 3g mode, χ = −0.03318 cm −1 K −1 ). For SnS, [19] SnSe, [36] the higher temperature coefficients may arise from the strong van der Waals interaction between the adjacent layers caused by their unique puckered crystal structures. For SnS, [19] SnSe, [36] the higher temperature coefficients may arise from the strong van der Waals interaction between the adjacent layers caused by their unique puckered crystal structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation